2016
DOI: 10.1016/j.kint.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood pressure is not associated with accelerated glomerular filtration rate decline in the general non-diabetic middle-aged population

Abstract: Although hypertension is a risk factor for end-stage renal disease, this complication develops in only a minority of hypertensive patients. Whether non-malignant hypertension itself is sufficient to cause reduced glomerular filtration rate (GFR) is unclear. We investigated whether elevated blood pressure (BP) was associated with accelerated GFR decline in the general population. The study was based on the Renal Iohexol-clearance Survey in Tromsø 6 (RENIS-T6), which included a representative sample of 1594 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…6,8,26 This finding suggested that arterial stiffness might be an early stage in the mechanism for accelerated GFR decline. We previously reported that baseline conventional BP per se did not accelerate age-related GFR decline in the RENIS cohort, 19 and the current investigation found the same results for ABP (Table 3).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…6,8,26 This finding suggested that arterial stiffness might be an early stage in the mechanism for accelerated GFR decline. We previously reported that baseline conventional BP per se did not accelerate age-related GFR decline in the RENIS cohort, 19 and the current investigation found the same results for ABP (Table 3).…”
Section: Discussionsupporting
confidence: 86%
“…38 In the current study, ambulatory PP was not a predictor of GFR decline, which confirmed our previous analyses based on baseline conventional BP. 19 AASI remained a significant predictor of the same magnitude even when adjustments were made for ambulatory PP or other baseline ABP components in sensitivity analyses.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the RENIS-FU Study, we obtained a repeated GFR measurement after 2 weeks and within 2 months from a random sample of 86 participants. The mean coefficient of variation for the intraindividual variation in GFR was 4.2% (95% confidence interval, 3.4% to 4.9%) as recently reported (23).…”
Section: Measurementssupporting
confidence: 82%
“…In RENIS-FU, the CV of recalculated GFR from the remeasured single samples can be compared to the CV of interindividual day-to-day variation in GFR (2.6% vs 4.2%), established in a previous study of the same cohort. 34 By calculating the corresponding variance from the mean GFR observed in that analysis (94 mL/min), 34 we can estimate that~38% of the total day-to-day variance in GFR can be attributed to measurement error, and the rest, to intraindividual biological variation. This result should nevertheless be interpreted with caution because several authors have reported higher CVs for the total day-to-day variation, in the range of 5% to 10%.…”
Section: Discussionmentioning
confidence: 99%